What's trending in breathlessness research? Proceedings from the 8th Annual Meeting of the Breathlessness Research Interest Group. (December 2015) - Chin, CA; Butcher, H Holt; Spathis, A; Ryan, R; Johnson, M; Pattinson, K; Currow, D; Banzett, R; Yorke, J; Clayson, H; Macnaughton, J; Penfold, C; et al.
Abstract : Breathlessness remains a challenging symptom, common to a multitude of malignant and non-malignant diseases, for which there are limited effective therapies once disease control is optimized. The American Thoracic Society (ATS) statement on dyspnoea reports that: (i) progress in dyspnoea management has not matched progress in elucidating underlying mechanisms; (ii) there is a critical need for interdisciplinary translational research to connect dyspnoea mechanisms with treatments; and (iii) there is a need to validate dyspnoea measures as patient-reported outcomes for clinical trials. Research into the many dimensions of breathlessness and its significance to patients and their carers has increased in recent years. This meeting is convened yearly to bring together researchers across various disciplines including respiratory medicine, anaesthetics, medical humanities, engineering, and palliative care, to further understanding of the symptom, discuss new techniques and advances in research, and pave the way forward for future studies and interventions. The presentations generated much vibrant discussion amongst the multidisciplinary attendees and highlighted areas where care for breathless patients could be improved. This is a positive time for breathlessness research, with several ATS research priorities being addressed and it is clear that further studies and ensuing interventions are on the horizon.